2020
DOI: 10.1111/ijpo.12737
|View full text |Cite
|
Sign up to set email alerts
|

The association between fetal growth and neonatal adiposity in urban South African infants

Abstract: Summary Objective To examine associations between maternal body mass index (BMI), gestational weight gain (GWG) and fetal growth and neonatal adiposity in urban South Africans. Methods Maternal BMI was assessed at recruitment and GWG (kg/week) was calculated. Longitudinal fetal growth was measured via ultrasound and modelled using Superimposition by Translation and Rotation (SITAR). Neonatal adiposity was assessed using air displacement plethysmography or dual‐energy X‐ray absorptiometry. Multiple linear regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…This, and previous, findings from S1000 emphasise the need to prioritise preconception health of adolescent girls and young women to establish healthy dietary practices, body size and metabolic profiles prior to pregnancy [ 4 6 , 36 ]. However, in low-income settings such as Soweto, poverty and limited financial resources restrict access to diverse, high quality diets [ 37 ].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This, and previous, findings from S1000 emphasise the need to prioritise preconception health of adolescent girls and young women to establish healthy dietary practices, body size and metabolic profiles prior to pregnancy [ 4 6 , 36 ]. However, in low-income settings such as Soweto, poverty and limited financial resources restrict access to diverse, high quality diets [ 37 ].…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, while our study showed no association between E-DII scores and birth outcomes, we have previously demonstrated an inverse association between adherence to the “traditional” dietary pattern and birth size and neonatal adiposity [ 6 ]. In addition, we have provided evidence of a pathway for greater neonatal adiposity in this cohort via an effect of higher GWG on fetal growth—particularly at the abdominal circumference [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The trial was designed following the Standard Protocol Items (Recommendations for Interventional Trials (SPIRIT) 2013 statement). Through extensive qualitative (focus groups, in-depth individual interviews and stakeholder engagement)18–23 and epidemiological research,24–31 we identified our young women (18–28 years) as the target group given that a high proportion these women are already either overweight or obese and most will have their first child during this age range, and developed the intervention package. We initially opted for a cluster randomised study design in order to included community peer group sessions as part of the intervention.…”
Section: Methodsmentioning
confidence: 99%
“… 6 In addition, continued obesity and excessive gestational weight gain (GWG) during pregnancy are strongly predictive of fetal growth, birth weight and obesity risk in the offspring. 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…6 In addition, continued obesity and excessive gestational weight gain (GWG) during pregnancy are strongly predictive of fetal growth, birth weight and obesity risk in the offspring. [7][8][9] Adipose tissue is a metabolically active organ-it is a major source of inflammatory cytokines and can interfere with insulin signaling by causing defects in insulin cascade, eventually resulting in insulin sensitivity or resistance. 10 Furthermore, the location of adipose tissue deposition may determine metabolic activity and related effects, and risk for metabolic disease.…”
Section: Introductionmentioning
confidence: 99%